EANM guideline for harmonisation on molar activity or specific activity of radiopharmaceuticals: impact on safety and imaging quality - Gert Luurtsema; Verena Pichler; Salvatore Bongarzone; Yann Seimbille; Philip Elsinga; Antony Gee; Johnny Vercouillie (SpringerOpen, 2021)
Abstract This guideline on molar activity (Am) and specific activity (As) focusses on small molecules, peptides and macromolecules radiolabelled for diagnostic and therapeutic applications. In this guideline we describe the definition of Am and As, and how these measurements must be standardised and harmonised. Selected examples highlighting the importance of Am and As in imaging studies of saturable binding sites will be given, and the necessity of using appropriate materials and equipment will be discussed. Furthermore, common Am pitfalls and remedies are described. Finally, some aspects of Am in relation the emergence of a new generation of highly sensitive PET scanners will be discussed.